Tourism, economic growth & employment - McCatty, Machel ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2006)
Uses sectoral impact multipliers to estimate the impact on GDP and employment of the anticipated growth in the tourism sector during the period 2007-2011.